Distinct Signaling Properties of Mitogen-activated Protein Kinase Kinases 4 (MKK4) and 7 (MKK7) in Embryonic Stem Cell (ESC) Differentiation - Wang, Jingcai (American Society for Biochemistry and Molecular Biology, 2012)
Signal transduction pathways are integral components of the developmental regulatory network that guides progressive cell fate determination. MKK4 and MKK7 are upstream kinases of the mitogen-activated protein kinases (MAPKs), responsible for channeling physiological and environmental signals to their cellular responses. Both kinases are essential for survival of mouse embryos, but because of embryonic lethality, their precise developmental roles remain largely unknown. Using gene knock-out mouse ESCs, we studied the roles of MKK4 and MKK7 in differentiation in vitro. While MKK4 and MKK7 were dispensable for ESC self-renewal and pluripotency maintenance, they exhibited unique signaling and functional properties in differentiation. MKK4 and MKK7 complemented each other in activation of the JNK-c-Jun cascades and loss of both led to senescence upon cell differentiation. On the other hand, MKK4 and MKK7 had opposite effects on activation of the p38 cascades during differentiation. Specifically, MKK7 reduced p38 activation, while Mkk7(−/−) ESCs had elevated phosphorylation of MKK4, p38, and ATF2, and increased MEF2C expression. Consequently, Mkk7(−/−) ESCs had higher expression of MHC and MLC and enhanced formation of contractile cardiomyocytes. In contrast, MKK4 was required for p38 activation and Mkk4(−/−) ESCs exhibited diminished p-ATF2 and MEF2C expression, resulting in impaired MHC induction and defective cardiomyocyte differentiation. Exogenous MKK4 expression partially restored the ability of Mkk4(−/−) ESCs to differentiate into cardiomyocytes. Our results uncover complementary and interdependent roles of MKK4 and MKK7 in development, and identify the essential requirement for MKK4 in p38 activation and cardiomyocyte differentiation.